Fabrication of chitosan-integrated single-mode tapered optical fiber DENV II E protein sensor - Mohd Amin @ Mohd Nasir, Nadia (2020)
Globally, diseases infected by dengue virus (DENV) prevails among major public health problem, especially in tropical and sub-tropical areas. 500 000 people are estimated infected with severe dengue require hospitalization every year and 2.5% is estimated case fatality. Quantitative assessment by enzyme-linked immunosorbent assay (ELISA) is known to be used by laboratories to produce better clinical monitoring but it needs complex laboratories infrastructure as well as expertise to operate it. For the past decades, tapered single mode fiber has shown versatility and enticing sensitivity towards changes in its surrounding refractive index, making it suitable for sensing applications. In 2018, a research developing tapered optical fiber sensor targeting dengue virus envelope (E) protein originates from DENV II which is among 4 distinct DENV serotypes has been published. DENV II E protein is the interested determinant since it is located at the outermost of dengue virus structure, hence detecting the protein signifies the presence of the virus itself. As a result, high sensitivity and specificity within rapid detection 15 minutes is achieved. This biosensor is enhanced further by utilizing inorganic material which is graphene to facilitate greater surface area for sensing enhancement. However, graphene is known to have mild toxicity and its effect to DENV II E protein is yet to be determined. This study looks into the use of organic nanomaterial namely chitosan for enhancement of tapered fiber sensing response. A layer of chitosan was introduced to single mode tapered fiber functionalized for the detection of DENV II E protein. Tapered optical fiber was fabricated and functionalized using Sodium Hydroxide (NaOH), 3-(Aminopropyl) triethoxysilane (APTES), and Glutaraldehyde. Chitosan immersion time up to 60 minutes was then tested yielding working immersion time of 20 (CHIT20), 30 (CHIT30), 35 (CHIT35), 40 (CHIT40) and 45 minutes (CHIT45). Subsequently, the experiment proceeded with the immobilization of antibody. The immersion time for antibody was optimized for CHIT20, CHIT30, CHIT35, CHIT40 and CHIT45 at 25, 30, 33, 35 and 38 minutes, respectively. After that, different concentration of DENV II E protein solution ranging from 0.0nM to 1.0nM with increment of 0.2nM were introduced. Prior to that, optimum incubation time of DENV II E protein for CHIT20, CHIT30, CHIT35, CHIT40 and CHIT45 was observed at 30, 35, 38, 40 and 43 minutes respectively. The spectral shift with the introduction of DENV II E protein was then recorded and analyzed. This set of experiment was conducted in triplicates. Consistent red shift of spectra at increasing concentration is observed for CHIT20. It obeys the linear relationship between concentration and refractive index which altered the effective refractive index and caused the red shift. For CHIT30, CHIT35, CHIT40 and CHIT45, consistent red shift of spectra was also noted. Increment of the sensitivity value is observed as CHIT20, CHIT30 and CHIT35 recorded 6.28 nm/nM, 10.68 nm/nM and 14.19 nm/nM, respectively. However, the sensitivity decreased for CHIT40 and CHIT45 with corresponding value of 12.24 nm/nM and 11.34 nm/nM. From these values, it is noted that the best sensitivity obtained for the sensor is at CHIT35 with 14.19 nm/nM. The work proceeded with the investigation on limit of detection (LOD) and the sensor was tested with different concentration ranging from 0.1pM to 0.1µM. The Langmuir curve plotted from the findings denoted LOD of 1pM. In conclusion, this study highlights the feasibility of using organic nanomaterial which has better biocompatibility and environmental friendly for the enhancement of DENV II E protein detection.